2019
DOI: 10.1186/s12909-019-1627-6
|View full text |Cite
|
Sign up to set email alerts
|

Training medical students: victim’s perceptions of selectively screening women for intimate partner violence in health care settings

Abstract: Background Routine IPV screening is a controversial topic and there is no evidence to suggest that it improves the health outcomes of women. Consequently, understanding the socio-cultural dimensions, becomes essential to ensure that victims receive appropriate and local support. This study was conducted to gather the perceptions of victims of IPV on the relevance of raising the topic at health care facilities and to determine specific categories of women to target for screening by medical personne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
(31 reference statements)
1
15
0
1
Order By: Relevance
“… 24 Feder’s review has made a critically important contribution towards understanding what women want from HCPs. However, since 2006, there has been a great deal more research conducted in the area of violence against women, including in low-income and-middle income countries such as Jordan, 25 Nigeria, 26 Peru 27 and India. 28 The problem of IPA has received increasing global attention, as has the potential role of HCPs in addressing it.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Feder’s review has made a critically important contribution towards understanding what women want from HCPs. However, since 2006, there has been a great deal more research conducted in the area of violence against women, including in low-income and-middle income countries such as Jordan, 25 Nigeria, 26 Peru 27 and India. 28 The problem of IPA has received increasing global attention, as has the potential role of HCPs in addressing it.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating intimate partner violence education into healthcare professionals training has received support from healthcare staff and survivors of violence. A study in Kuwait involving 128 physicians and 238 nurses demonstrated that a majority of healthcare providers (82.4% nurses and 82.0% physicians) agreed with universally screening all patients for intimate partner violence to better identify domestic violence survivors (Fawole et al 2019). A study conducted in Nigeria, with women who had faced some form of intimate partner violence, reported that most women felt that medical practitioners should ask all patients who present to the healthcare facility if they are facing domestic violence (Fawole et al 2019).…”
Section: Importance Of Training Healthcare Providers About Intimate Pmentioning
confidence: 99%
“…A study in Kuwait involving 128 physicians and 238 nurses demonstrated that a majority of healthcare providers (82.4% nurses and 82.0% physicians) agreed with universally screening all patients for intimate partner violence to better identify domestic violence survivors (Fawole et al 2019). A study conducted in Nigeria, with women who had faced some form of intimate partner violence, reported that most women felt that medical practitioners should ask all patients who present to the healthcare facility if they are facing domestic violence (Fawole et al 2019). The survivors of violence acknowledged that screening might not help women who were afraid to speak out; however, they felt optimistic that it might offer solutions to help stop the cycle of violence while providing holistic care for the patients (Fawole et al 2019).…”
Section: Importance Of Training Healthcare Providers About Intimate Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate healthcare provider training is a frequently cited barrier to addressing IPV in practice (Dyer & Abildso, 2019; Fawole et al, 2019; Rees et al, 2014). In order for nurses to screen for IPV and appropriately respond to survivors, it is important for nurses to receive adequate and effective IPV education and training (Anderzen‐Carlsson et al, 2018), as well as well‐designed “prequalification” healthcare provider training (i.e., for students) (Crombie et al, 2017; WHO, 2013).…”
Section: Introductionmentioning
confidence: 99%